Implikasi Sosial dan Ekonomi dari PHK Massal - Roudatus Solihah; Ali Alamginto; Oktavia Theresia Ompu Sunggu (Badan Penerbit STIEPARI Press, 2023)
Mass layoffs (PHK) are a phenomenon that often impacts the employment sector and has a major impact on a number of social and economic factors. Many factors, such as business reorganization, the current economic climate, or technological advances leading to job automation, can lead to mass layoffs. The research in the article uses a qualitative approach with descriptive methods and data collection is carried out using various literature obtained from journals and the Internet in the process of searching for data via internet media. In the first quarter of 2023, West Java will be the province with the most layoffs, namely 5,603 workers. And followed by Central Java with 4,887 laid off workers, and Banten with 2,342 workers.